2020
DOI: 10.1186/s13075-020-02340-7
|View full text |Cite
|
Sign up to set email alerts
|

The Janus kinase 1/2 inhibitor baricitinib reduces biomarkers of joint destruction in moderate to severe rheumatoid arthritis

Abstract: Background Tissue released blood-based biomarkers can provide insight into drug mode of action and response. To understand the changes in extracellular matrix turnover, we analyzed biomarkers associated with joint tissue turnover from a phase 3, randomized, placebo-controlled study of baricitinib in patients with active rheumatoid arthritis (RA). Methods Serum biomarkers associated with synovial inflammation (C1M, C3M, and C4M), cartilage degradation (C2M), bone resorption (CTX-I), and bone formation (osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…Consistent with the results of preclinical studies, a recent analysis of serum biomarkers in blood samples from 240 patients participating in RA-BUILD showed that treatment with baricitinib 4 mg once daily significantly reduced serum biomarkers of joint synovial inflammation and tissue destruction [42]. At week 4, serum levels of three different biomarkers of synovial inflammation (C1M, C3M and C4M) had decreased by 12-21%, depending on the biomarker (p < 0.01), and these reductions were maintained at week 12 (reductions of 11-27%; p < 0.001).…”
Section: Inhibition Of Bone Losssupporting
confidence: 65%
“…Consistent with the results of preclinical studies, a recent analysis of serum biomarkers in blood samples from 240 patients participating in RA-BUILD showed that treatment with baricitinib 4 mg once daily significantly reduced serum biomarkers of joint synovial inflammation and tissue destruction [42]. At week 4, serum levels of three different biomarkers of synovial inflammation (C1M, C3M and C4M) had decreased by 12-21%, depending on the biomarker (p < 0.01), and these reductions were maintained at week 12 (reductions of 11-27%; p < 0.001).…”
Section: Inhibition Of Bone Losssupporting
confidence: 65%
“…The excellent clinical results and bone-erosion-reducing effects with BAR have been reported [ 198 ]. Thudium et al [ 169 ] conducted a subgroup analysis of the RA-BUILD study and have reported changes in bone metabolism markers in 240 subjects. After 12 weeks of the BAR treatment, osteogenic markers did not change significantly, whereas bone resorption markers were significantly reduced.…”
Section: Effects Of Ra Treatment On Bone Metabolismmentioning
confidence: 99%
“…It was discovered that treatment with baricitinib reduced the circulating biomarkers linked with the destruction of joint tissue, which led to a simultaneous improvement in clinical symptoms of RA. 73 It was discovered by Farr and colleagues that a JAKi inhibited the production of the pro-inflammatory secretome by senescent cells. Studies conducted in vitro demonstrated that senescent cell-conditioned medium led to increased osteoclastogenesis by inhibiting osteoblast mineralization and enhancing osteoclast progenitor survival.…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%
“…Within the context of a placebo‐controlled, randomized phase 3 trial of baricitinib in active RA patients, Tudium et al evaluated the related biomarkers with the turnover of joint tissue. It was discovered that treatment with baricitinib reduced the circulating biomarkers linked with the destruction of joint tissue, which led to a simultaneous improvement in clinical symptoms of RA 73 . It was discovered by Farr and colleagues that a JAKi inhibited the production of the pro‐inflammatory secretome by senescent cells.…”
Section: Dmards Therapy and Bone Turnover Markersmentioning
confidence: 99%